MOB1A - Carmona, Bruno (2018)
The accuracy of cell division is fundamental for the maintenance of cell ploidy and genomic stability. During cell division, many events, like DNA replication, chromosome segregation, mitosis completion, and cytokinesis, must be tightly controlled. The deregulation of these events is closely associated with severe pathology. Among other factors, the accuracy of cell division relies on the correct placement of the division plane which is dependent on the polarity axis. Both in unicellular organisms and in metazoan, the cell spindle position is regulated to be perpendicular or planar to the division plane, allowing this way to equally segregate the chromosomes between the two daughter cells.